Marketing Strategy for OEMAH ETNIK Fashion Brand in New Wave Marketing Concept - Kurnia, Raden Hayuningtyas Putrinda; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2015)
OEMAH ETNIK was born in 2013 when fashion industry with traditional fabrics is being developed in Indonesia. OEMAH ETNIK products have modern designs that will suit within local and international markets. OEMAH ETNIK is running business-to-consumer that are aligned with their vision and mission, which is to popularize the Indonesian cultural heritage to youth Indonesian people in particular. By analyzing the internal and external factors, and marketing methods that are being undertaken by OEMAH ETNIK, it appears that the main challenges and root of problems lies in the lack of marketing strategy that leads OEMAH ETNIK facing difficulties in developing their business and competing in a very competitive fashion market that is growing rapidly in Indonesia. Marketing strategy is one of important elements in improving company performance business. By doing a good marketing, OEMAH ETNIK can build brand awareness and increase the number of customers. As the development of technology, business challenges require changes in both pattern and behavior of products from the standpoint of Technology, Socio-Cultural, Economic, Political and Market. The global market anticipates this transformation by transitioning from legacy to new wave marketing era. New wave marketing brought a horizontal approach concept to its customers. Customers are treated as equals and given the opportunity to actively participate, and demand company to develop marketing system to have more personal approach, building character, bond & collaborate closer with customer in order to form a marketing system that is more personal. According to this concept, produce a change in marketing strategy and improvements on OEMAH ETNIK Business Model which also included the implementation of 12 elements in new wave marketing, directs them to a new business model to synergize between the recommendation and marketing method designed by the author as a solution.Â Keywords: Fashion, Indonesia Traditional Textile, New Wave Marketing, OEMAH ETNIK, Marketing Strategy